Mespilus germanica (MG) and Tribulus terrestris (TT) Used as Biosorbents for Lead Removal from Aqueous Solutions: Adsorption Kinetics and Mechanisms - Majid Ehteshami; Hamidreza Zolfaghari; Marjan Salari; Ehsan Teymouri (Advances in Materials Science and Engineering)
Today, most countries around the globe are facing water resources restrictions, and it is predicted freshwater resources will be more valuable than oil wells in the next century. In the present study, the ability of lead removal using both powders of Mespilus germanica (MG) and Tribulus terrestris (TT) seeds and optimization of the adsorption process have been investigated. Four main parameters were selected for experimental design, namely, pH, time of contact, the ratio of adsorbent to solution volume, and initial concentration of lead in solution, and the optimization of effective parameters on lead adsorption was performed based on central composite design (CCD) under response surface methodology (RSM). According to the statistical results, the proposed model for MG and TT is confirmed with 0.95 and 0.96 correlation coefficient and 0.92 and 0.94 adjusted correlation coefficient, respectively. The results of parameter optimization also showed that both adsorbents have the acceptable ability to adsorb lead from aqueous solutions. Under the optimum conditions with the initial lead concentration of 10 mg/l, MG powder had better performance in lead adsorption of 96.04%, and TT powder also had an acceptive performance of 93.20%. Moreover, the MG and TT adsorbents have the most accordance with the Freundlich and D-R isotherms, respectively.